Upgraded - Clarke, Neil 1966- (Wyrm Publishing, 2014)
Better . . . Stronger . . . Faster . . . The doctors rebuilt Hugo Award-winning editor Neil Clarke and made him a cyborg. Now he has assembled this anthology of twenty-six original cyborg stories by Greg Egan, Madeline Ashby, Elizabeth Bear, Peter Watts, Ken Liu, Robert Reed, Yoon Ha Lee, and more!